1999
DOI: 10.1126/science.283.5402.655
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-Dependent Formation of β 2 Adrenergic Receptor-Src Protein Kinase Complexes

Abstract: The Ras-dependent activation of mitogen-activated protein (MAP) kinase pathways by many receptors coupled to heterotrimeric guanine nucleotide binding proteins (G proteins) requires the activation of Src family tyrosine kinases. Stimulation of beta2 adrenergic receptors resulted in the assembly of a protein complex containing activated c-Src and the receptor. Src recruitment was mediated by beta-arrestin, which functions as an adapter protein, binding both c-Src and the agonist-occupied receptor. beta-Arrestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
1,192
4
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,369 publications
(1,254 citation statements)
references
References 36 publications
48
1,192
4
10
Order By: Relevance
“…MAP and PI3-kinase Differential effects of beta-gamma binding proteins Z Li et al activities have recently been shown to be inhibited by activated Gbg-BARK1. 22,23 As phosphorylation of phosducin has been shown to abolish the effects of phosducin on G protein function, 14,15,24,25 the deletion of the phosphorylation sites at amino acids 6, 36 and 54 by N-terminal truncation was introduced in the mutant used in the present study. This modification resulted in a phosducin mutant producing consistent effects in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAP and PI3-kinase Differential effects of beta-gamma binding proteins Z Li et al activities have recently been shown to be inhibited by activated Gbg-BARK1. 22,23 As phosphorylation of phosducin has been shown to abolish the effects of phosducin on G protein function, 14,15,24,25 the deletion of the phosphorylation sites at amino acids 6, 36 and 54 by N-terminal truncation was introduced in the mutant used in the present study. This modification resulted in a phosducin mutant producing consistent effects in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of c-Src in cells expressing GFP-P52 and GFP-P66 demonstrates that c-Src activity can be up-regulated by an adaptor protein. This is not so surprising because several molecules with no intrinsic catalytic activity have been reported to be an activator for c-Src or the Src family tyrosine kinases: it includes hepatitis B virus HBx protein (Klein & Schneider 1997), HIV virus Nef protein (Moare® et al 1997), synapsin I (Onofri et al 1997), b-arrestin 1 (Luttrell et al 1999), and TRAF6 (Wong et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthexmore, arrestin-mediated endocytosis enhances rnitogenic signalling (Lin et al, 1998). A very recent study has demonstrated that the non-receptor tyrosine kinase Src binds to the arrestin protein through its SH3 domain (Luttrell et al, 1999 PH domains have been found to be important in GPCR signalling. The interaction between the Gpy dimer and BARKs is mediated by PH domain (Touhara et al, 1994;.…”
Section: Grb2 and L A D S To Ras Activation (Kraneneburg Etmentioning
confidence: 99%
“…Dynarnin may dso be involved in signal transduction (Umtia et al, 1997). Dynarnin has a proline-rich region that contains several SH3 binding motifs in the carboxyl-terminal portion of the protein that are able to bind to distinct subsets of SH3 domain containing proteins (Scaife and Margolis, 1997 Grabs et al, 1997;Lichte et al, 1992 (Luttrell et al, 1999 domains (Sudol,I996b). WW domains, however, also require a tyrosine residue in th& recognition motif (PpXY) (Sudol, 1996b depending on the arnino-and carboxyl-orientation of the protein Feng et al, 1995;Yu et al, 1994).…”
Section: Grb2 and L A D S To Ras Activation (Kraneneburg Etmentioning
confidence: 99%